Cyclical and Stuctural Variation in Resource Reallocation: Evidence for Europe - Eric Jan Bartelsman; Paloma López-García; Giorgio Presidente (Tinbergen Institute, 2018)
This paper uses cross-country micro-aggregated data on rm dynamics and productivity from the ECB CompNet database to provide empirical evidence on factor reallocation in the EU. The analysis fi nds that reallocation is towards more productive firms although the magnitude varies across countries and over time. Variation in reallocation is related to structural di fferences in firm size distribution across countries as well as to variation in labor and product market institutions. Productivity enhancing reallocation generally rises in downturns but, similar to findings for the US, it did not pick up in the great recession. The sharp drop in exports and tightness in credit markets are seen to provide a partial explanation for this lack of a silver lining.
Keywords: C8; D24; E32; F4; 330; Great Recession; Factor Reallocation